2022
DOI: 10.3390/ijms23137449
|View full text |Cite
|
Sign up to set email alerts
|

Postischemic Neuroprotection of Aminoethoxydiphenyl Borate Associates Shortening of Peri-Infarct Depolarizations

Abstract: Brain stroke is a highly prevalent pathology and a main cause of disability among older adults. If not promptly treated with recanalization therapies, primary and secondary mechanisms of injury contribute to an increase in the lesion, enhancing neurological deficits. Targeting excitotoxicity and oxidative stress are very promising approaches, but only a few compounds have reached the clinic with relatively good positive outcomes. The exploration of novel targets might overcome the lack of clinical translation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
(105 reference statements)
0
6
0
Order By: Relevance
“…Store-operated Ca 2+ entry (SOCE) mediated by calcium release-activated calcium (CRAC) channels also contributes to increased intracellular calcium and CRAC channel inhibitor improves TBI outcome by inhibiting neuroinflammation [ 46 ]. Another study found that blocking IP3 receptor with 2-APB significantly reduced infarcts in a cerebral ischemia model [ 47 ]. In this study, BDEV can significantly depolarize neurons and endothelial cells and cause cytoplasmic calcium overload in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Store-operated Ca 2+ entry (SOCE) mediated by calcium release-activated calcium (CRAC) channels also contributes to increased intracellular calcium and CRAC channel inhibitor improves TBI outcome by inhibiting neuroinflammation [ 46 ]. Another study found that blocking IP3 receptor with 2-APB significantly reduced infarcts in a cerebral ischemia model [ 47 ]. In this study, BDEV can significantly depolarize neurons and endothelial cells and cause cytoplasmic calcium overload in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Store-operated Ca 2+ entry (SOCE) mediated by calcium release-activated calcium (CRAC) channels also contributes to increased intracellular calcium and CRAC channel inhibitor improves TBI outcome by inhibiting neuroin ammation [44]. Another study found that blocking IP3 receptors with 2-APB signi cantly reduced infarcts in a cerebral ischemia model [45]. In this study, BDEV can signi cantly depolarize neurons and endothelial cells and cause cytoplasmic calcium overload in vitro.…”
Section: Discussionmentioning
confidence: 68%
“…Consequently, the pharmacological inhibition of neuronal connexin GJC may offer a strategy for protecting against secondary cell death in such disease contexts. Indeed, several GJC inhibitors, including MFQ, quinine, quinidine, flufenamic acid, 2-APB, and meclofenamic acid, have shown neuroprotective effects by targeting Cx36 22,[41][42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the pharmacological inhibition of neuronal connexin GJC may offer a strategy for protecting against secondary cell death in such disease contexts. Indeed, several GJC inhibitors, including MFQ, quinine, quinidine, flufenamic acid, 2-APB, and meclofenamic acid, have shown neuroprotective effects by targeting Cx36 22,4144 . Despite its pharmacological promise and its pivotal role in disease-related neuroprotection, the molecular mechanism of Cx36 channel inhibition remains largely elusive.…”
Section: Discussionmentioning
confidence: 99%